2021
DOI: 10.1002/asia.202100719
|View full text |Cite
|
Sign up to set email alerts
|

Trinuclear Organometallic Pt−Ir−Pt Complexes: Insights into Photophysical Properties, Amino Acid Binding and Protein Sensing

Abstract: The rational synthesis of trinuclear emissive organometallic complexes with two equivalent platinum(II) centres appended to the ancillary substituted 2,2′‐bipyridyl ligand of the cyclometalated iridium(III) centre is reported here. The alkynyl‐platinum moiety and cyclometalated iridium(III) centres have been separated through a non‐conjugated CH2−O−CH2 linkage. The emission titration with amino acids reveals that the complexes sense free amino acids. The luminescence sensing of BSA is thus attributed to the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Earlier efforts to engineer the HOMO–LUMO gap were in the line of ligand modification and through systematic inclusion of emissive or non-emissive metal centers at the cyclometalated or ancillary ligand ends. We have shown that proper choice of the second metal center helps in designing multinuclear metal complexes, where the cyclometalated Ir­(III) core remains as the emissive center and the other metal center(s) provide binding sites for amino acids and nucleic acids. Our recent interest in the synthesis of multimetallic complexes recommended methods to manipulate the emission and redox properties based on electron transfer among the metal centers. …”
Section: Introductionmentioning
confidence: 99%
“…Earlier efforts to engineer the HOMO–LUMO gap were in the line of ligand modification and through systematic inclusion of emissive or non-emissive metal centers at the cyclometalated or ancillary ligand ends. We have shown that proper choice of the second metal center helps in designing multinuclear metal complexes, where the cyclometalated Ir­(III) core remains as the emissive center and the other metal center(s) provide binding sites for amino acids and nucleic acids. Our recent interest in the synthesis of multimetallic complexes recommended methods to manipulate the emission and redox properties based on electron transfer among the metal centers. …”
Section: Introductionmentioning
confidence: 99%
“…The detailed synthetic procedure is outlined in Scheme 1. 15 The complexes are characterized by CHN analysis, ESI-MS (Fig. S1†) and 1 H NMR, 13 C NMR, 195 Pt NMR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ligand L was synthesized through a multistep procedure as detailed in our prior research article. [42][43] Subsequently, L reacts with Ru(bpy)₂Cl₂ in a solvent mixture of ethanol:water (3:1) at 80°C for 4h under inert conditions, resulting in the formation of complex Ru1 as a photosensitizing center. Ru1 undergo a Cu(I)-catalyzed cycloaddition reaction using Cu(CH₃CN)₄PF₆, Cu(0), and DIPEA in a DCM:Methanol (4:1) solvent at 60°C for 5 days, to afford complex Ru2.…”
Section: Synthesismentioning
confidence: 99%